2020
DOI: 10.3389/fchem.2020.560274
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Chaos in the CSTR Bray–Liebhafsky Oscillator-Specific Flow Rate Dependence

Abstract: Dynamic states with intermittent oscillations consist of a chaotic mixture of large amplitude relaxation oscillations grouped in bursts, and between them, small-amplitude sinusoidal oscillations, or even the quiescent parts, known as gaps. In this study, intermittent dynamic states were generated in Bray-Liebhafsky (BL) oscillatory reaction in an isothermal continuously-fed, well-stirred tank reactor (CSTR) controled by changes of specific flow rate. The intermittent states were found between two regular perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Therefore, from the preceding analysis, it is clear that the system does not exhibit chaotic behaviour for any parameter values that we deem to be realistic. This is a particularly interesting observation as it has been reported that the Bray–Liebhafsky reaction is able to exhibit chaotic oscillations when completed under continuous stirred–tank reactor conditions (CSTR) [32,33]. The fact that chaos cannot be observed in our proposed model is a limitation of the system and means it is not suitable for modelling the Bray–Liebhafsky reaction in CSTR environments; however, it can still be a good candidate for modelling open reactions [34,35].…”
Section: Further Analysis Of the Four-variable Modelmentioning
confidence: 98%
“…Therefore, from the preceding analysis, it is clear that the system does not exhibit chaotic behaviour for any parameter values that we deem to be realistic. This is a particularly interesting observation as it has been reported that the Bray–Liebhafsky reaction is able to exhibit chaotic oscillations when completed under continuous stirred–tank reactor conditions (CSTR) [32,33]. The fact that chaos cannot be observed in our proposed model is a limitation of the system and means it is not suitable for modelling the Bray–Liebhafsky reaction in CSTR environments; however, it can still be a good candidate for modelling open reactions [34,35].…”
Section: Further Analysis Of the Four-variable Modelmentioning
confidence: 98%